2022
DOI: 10.3390/ph15050622
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib May Inhibit Myofibroblast Differentiation from Rheumatoid-Fibroblast-like Synoviocytes Induced by TGF-β and IL-6

Abstract: During rheumatoid arthritis (RA), the pathogenic role of resident cells within the synovial membrane is suggested, especially for a population frequently referred to as fibroblast-like synoviocytes (FLSs). In this study, we assess the markers of myofibroblast differentiation of RA-FLSs by ex vivo observations and in vitro evaluations following the stimulation with both TGF-β and IL-6. Furthermore, we investigated the possible inhibiting role of tofacitinib, a JAK inhibitor, in this context. Myofibroblast diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Western blotting was conducted as previously described [ 22 ]. The total proteins of synovial tissue and cells were extracted and quantified with a BCA protein concentration kit (Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was conducted as previously described [ 22 ]. The total proteins of synovial tissue and cells were extracted and quantified with a BCA protein concentration kit (Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, translational findings suggested that the administration of tofacitinib could improve some pathogenic mechanisms associated with accelerated atherosclerosis [ 28 30 ]. In fact, the inhibitory effects of tofacitinib have been recently shown on myofibroblast differentiation by transforming growth factor β and IL-6 [ 29 ]. Both in vitro and in vivo findings showed that tofacitinib may have anti-angiogenic properties [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…and alpha actin-2 ( Acta2 ), and their expression was decreased by dissociation of mitochondrial HK2. A myofibroblast signature was described in RA FLS from a high-inflammation synovium ( 63 , 64 ). Other genes like periostin were already associated with migration and invasion of synoviocytes ( 65 ).…”
Section: Discussionmentioning
confidence: 99%